Pre-energy reasoning in preschool children - DIMITRIS KOLIOPOULOS; VASILIA CHRISTIDOU; IRINI SYMIDALA; ΜARIA KOUTSIOUBA (Metaichmio Publications, 2009)
The research presented in this paper explores the degree to which preschool children have the ability to use mental representations which constitute precursor energy models. Twenty-five children (10 boys and 15 girls) participated in the study. They were presented with two different phenomenological situations considered as important for the establishment of pre-energy reasoning: the movement of a toy car with the use of batteries and the movement of an identical car with the use of a spring. The children were involved in personal, semi-structured interviews, which aimed at eliciting their explanations about the movement of the two cars. The analysis of children's explanations reveals that they tend to explain the movement of cars in both phenomenological situations in naturalistic terms. These naturalistic explanations were mainly agentive, that is they regard the batteries and the spring correspondingly as external agents causing the cars' movement. The major percentage of agentive naturalistic explanations was given in terms of the function of the objects under discussion, while a number of them were formulated in terms of distribution. These findings designate a developing understanding of physical causality and a pre-energy character in children's reasoning, since they are capable of accounting for the two phenomenological situations in terms of object chains. Therefore, an attempt to introduce the aspect of energy transfer in preschool education could be considered.